Evaluasi Kemampuan Alat Gali Muat untuk Pencapaian Target Produksi Limestone Menggunakan Metode Overall Equipment Effectiveness (OEE) pada Bukit Karang Putih PT. Semen Padang - Fachri Diwanda; Tri Gamela Saldy (Journals Mining Engineering : Bina Tambang, 2023)
Observation data for limestone production in the PNBP block of PT. Semen Padang did not reach the target in August 2022 due the low effective working time of the excavator, which was 278.7 hours/month for the Hitachi EX 2500 and 296 hours/month for the Caterpillar 6030 Excavators out of 558 hours/month available working time. Analysis of the productivity of working hours of tools needs to be done to overcome these problems,, one of which is the Overall Equipment Effectiveness (OEE) method to measure tool performance and fishbone diagrams to identify obstacles during production. The results showed that the actual productivity was 601,527 tons/month. Fishbone diagram analysis shows that there are inhibiting factors that cause high loss time, including method, equipment, environment, and human factors. After improving the standby delay time value of the Hitachi EX 2500 (EH 06) Excavator and Caterpillar 6030 (EC 03) excavator, the total loss time was reduced to 28.8 hours/month and 29.2 hours/month, respectively. increased tool uptime. Thus, the OEE value increased to 40% and 43%. Thus, overall limestone production increased by 1,317,693 tons/month, which means the target has been reached. The increase in the OEE value is still low when compared to world class standard OEE values, at 85% and still needed improvement.